Monthly Mean Sea Ice Data from the Polar Ice Prediction System, the Regional Polar Ice Prediction System - Barents Sea and the Regional Polar Ice Prediction System - Greenland Sea - Posey, P. G.; Preller, R. H. (1991)
The Polar Ice Prediction System (PIPS), the Regional Polar Ice Prediction System-Barents (RPIPS-B) and the Regional Polar Ice Prediction System-Greenland (RPIPS-G) are all operational sea ice forecasting systems that have been run daily at the Fleet Numerical Oceanography Center (FNOC) since September 1987, June 1989 and October 1991, respectively. The basis for all three models is the Hibler ice model (Hibler, 1979;1980). The ice models are driven by monthly mean ocean currents and deep ocean heat fluxes derived from the Hibler and Bryan (1987) coupled ice-ocean model. They are also driven by atmospheric forcing from the Navy Operational Global Atmospheric Prediction System (NOGAPS) (Rosmond, 1981; Hogan et al., 1990). Each day a 24-hour forecast of PIPS, RPIPS-B and RPIPS-G is submitted and archived by Naval Oceanographic and Atmospheric Research Laboratory (NOARL). This technical note contains monthly mean values of geostrophic winds, ice drift, ice thickness and ice concentration derived from the PIPS and RPIPS-B 24-hour forecast from 1990 and 1991; and 24-hour forecast form RPIPS-G from 1991.